2017
DOI: 10.1002/2017ja024131
|View full text |Cite
|
Sign up to set email alerts
|

Statistical characterization of the large‐scale structure of the subauroral polarization stream

Abstract: The subauroral polarization streams (SAPS) are latitudinally narrow regions of westward directed flows observed equatorward of the evening sector auroral oval. Previous studies have shown that SAPS generally occur during geomagnetically disturbed conditions and exhibit a strong dependence on geomagnetic activity. In this paper, we present the first comprehensive statistical study of SAPS using measurements from the U.S. midlatitude Super Dual Auroral Radar Network (SuperDARN) radars. The study period spans Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
82
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(96 citation statements)
references
References 47 publications
14
82
0
Order By: Relevance
“…We have also presented a model of the equatorward edge of electron precipitation with which the subauroral potential model can be combined. A summary of statistical results is as follows: The variation of SAPS latitude with activity level and MLT agrees with previous statistical studies (e.g., Erickson et al, ; Foster & Vo, ; Kunduri et al, ; Wang et al, ). SAPS latitude decreases closer to midnight due to the decreasing latitude of the auroral boundary.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We have also presented a model of the equatorward edge of electron precipitation with which the subauroral potential model can be combined. A summary of statistical results is as follows: The variation of SAPS latitude with activity level and MLT agrees with previous statistical studies (e.g., Erickson et al, ; Foster & Vo, ; Kunduri et al, ; Wang et al, ). SAPS latitude decreases closer to midnight due to the decreasing latitude of the auroral boundary.…”
Section: Discussionsupporting
confidence: 88%
“…The total subauroral potential drop also maximizes at 1800–2000 MLT. Near solstice, the total subauroral potential drop and SAPS width is maximized between 1800 and 2000 MLT, but the maximum drifts are found between 1600 and 1800 MLT (see Figures and ). The latitudinal shape of the median SAPS drift profile is MLT dependent (see Figure ). SAPS drifts have a higher amplitude during equinoxes than during solstices (see Figures and ). There is an approximately linear decay in the maximum westward SAPS drifts in MLT from dusk to midnight in agreement with previous statistical studies (Erickson et al, ; Foster & Vo, ; Kunduri et al, ) and in disagreement with the SAPS event observed simultaneously by SuperDARN radars over 6 hr of MLT and 3 hr in universal time in Clausen et al (), which decayed exponentially (see Figure ). SAPS amplitude and width in the dusk sector vary inversely with F10.7 solar radio flux. (see Figure )…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This polarization electric field leads to a strong E x B drift, which forms the fast westward drifting SAPS flow (Kunduri et al, 2017Landry & Anderson, 2018;Lejosne et al, 2018). During the growth phase, the R1/R2 currents progress equatorward as the polar cap expands.…”
Section: Discussionmentioning
confidence: 99%
“…The midlatitude expansion of SuperDARN radars over the past 10 years has provided new opportunities to study midlatitude ionospheric convection over large areas and with unprecedented spatial resolution and statistical significance. However, most studies of midlatitude convection using the midlatitude SuperDARN radars have focused on features that occur during geomagnetically disturbed conditions such as the high‐speed subauroral polarization streams (Clausen et al, ; Kunduri et al, , ; Oksavik et al, ). Only a handful of studies have focused on quiet time midlatitude convection (Baker et al, ; Zou & Nishitani, ).…”
Section: Introductionmentioning
confidence: 99%